Functions of Music Making Under Lockdown: A Trans-Historical Perspective Across Two Pandemics - Chiu, Remi (Frontiers in Psychology, 2020)
This paper describes how music fulfills two of its broadly recognized functions—“mood regulation” and “social cohesion”—in times of pandemics and social isolation. Through a trans-historical comparison of the musical activities of the Milanese during an outbreak of plague in 1576 with the musical activities observed during the COVID lockdowns in 2020 (such as balcony-singing and playlist-making), this paper suggests a framework for understanding the role of music in the care of the biological body and the social body in times of medical disaster.